Book Review: Critical Issues in International Refugee Law - Rickwood, Roger (The Journal of Public Policy, Administration, and Law, 2011)
Critical Issues in International Refugee Law is a must read for advocates of progressive refugee law. The book offers solutions to prevent the fragmentation and the hollowing out of traditional concepts of refugee protection in an age where, increasingly, refugee applicants are unwanted and seen as economic interlopers and security threats. The author summarizes a 2008 workshop at York University where legal experts, practitioners and adjudicators explored various states‘ practices in the interpretation of the International Convention and complementary protection processes collateral to the Convention. The book demonstrates the value of organizing a focused workshop utilizing discussions among expert participants